2021
DOI: 10.1186/s12909-021-02791-9
|View full text |Cite
|
Sign up to set email alerts
|

Student support systems for undergraduate medical students during the COVID-19 pandemic: a systematic narrative review of the literature

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has boosted medical students’ vulnerability to various problems. Given the stressful nature of medical disciplines, considerable attention must be paid to student support systems during pandemics. This study aimed to review the current literature regarding medical student support systems systematically. Methods We performed a systematic review of six databases and grey literature sources i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 55 publications
(65 reference statements)
1
32
0
Order By: Relevance
“…This pandemic is an opportunity to change things. A narrative review on student support systems for undergraduate medical students during the COVID-19 pandemic found 10 studies: the two main themes were academic support and mental health support [34] . French medical universities had a critical gap compared to some countries.…”
Section: Discussionmentioning
confidence: 99%
“…This pandemic is an opportunity to change things. A narrative review on student support systems for undergraduate medical students during the COVID-19 pandemic found 10 studies: the two main themes were academic support and mental health support [34] . French medical universities had a critical gap compared to some countries.…”
Section: Discussionmentioning
confidence: 99%
“…Many universities have ramped up online teaching and supervision to cater to the physical distancing and quarantine requirements induced by the COVID‐19 pandemic, as evidenced through a recent systematic review. 8 This transition was not unique to medicine but was widely experienced because of the normally high volume of training occurring in clinical settings. While this transition has been a blessing in many ways, such as enabling continuation of training, it also has some pitfalls including reduced collaborative learning, feelings of distress for tutors associated with diminished feedback when students' cameras are switched off, and challenges in building rapport with patients during clinical encounters.…”
Section: Introductionmentioning
confidence: 99%
“…While this transition has been a blessing in many ways, such as enabling continuation of training, it also has some pitfalls including reduced collaborative learning, feelings of distress for tutors associated with diminished feedback when students' cameras are switched off, and challenges in building rapport with patients during clinical encounters. 8 , 9 A Libyan study that investigated over 3000 medical students' experiences of the pandemic found that students paid less attention during online lectures. 10 Issues of Zoom burnout and Zoom fatigue have also been recently raised, caused by the need for attentiveness to nonverbal cues and the constant awareness of what a person is doing while the Zoom camera is on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, so that the learning process using e-learning can be effective, the existing obstacles must be overcome. In addition, in developing this learning, cultural and contextual learning must be considered [17].…”
Section: Resultsmentioning
confidence: 99%